2014
DOI: 10.1186/2046-0481-67-2
|View full text |Cite
|
Sign up to set email alerts
|

Congenital cataracts in an Ayrshire herd: a herd case report

Abstract: An Ayrshire dairy herd was investigated for occurrence of ocular abnormalities in new-born calves. Ophthalmic examinations were performed on all the animals in the herd and 26% of them were diagnosed with bilateral cataracts. Cataracts varied in extent and severity but the majority were restricted to the lens nucleus. Epidemiological analysis showed the prevalence was higher in male animals and lower in animals born to heifers. A family tree was designed but no genetic impact of dam lines was evident. Sire dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Cataracts in cattle have been reported sporadically (OMIA-9913) and the mode of inheritance has been an object of debate [21] , [22] . A recent case of congenital cataract in Ayrshire cattle with a high prevalence in a single herd was reported, but a genetic etiology has not been demonstrated [23] , as well as in a population of Swiss calves [24] . One study has reported a dominant mutation in the FNB1 gene as the cause of Marfan syndrome in cattle accompanied by cataract beside other defects [25] .…”
Section: Introductionmentioning
confidence: 97%
“…Cataracts in cattle have been reported sporadically (OMIA-9913) and the mode of inheritance has been an object of debate [21] , [22] . A recent case of congenital cataract in Ayrshire cattle with a high prevalence in a single herd was reported, but a genetic etiology has not been demonstrated [23] , as well as in a population of Swiss calves [24] . One study has reported a dominant mutation in the FNB1 gene as the cause of Marfan syndrome in cattle accompanied by cataract beside other defects [25] .…”
Section: Introductionmentioning
confidence: 97%
“…Unilateral or bilateral congenital cataracts with focal to diffuse opacities of the lens cause impaired vision to blindness in young cattle [1,2]. In cattle, cases of congenital cataracts were reported in many different breeds including Holstein [35], Swiss Brown [6], Jersey [7], Hereford [8], Aberdeen Angus [8], Shorthorn [9], Ayrshire [10] and Romagnola [11]. Prevalences were up to 34% in Holsteins [5], 79.5% [12] and 31% in a Canadian Holstein dairy herd [13].…”
Section: Introductionmentioning
confidence: 99%
“…Besides hereditary cataracts, opacities also occur as part of multisystemic disorders or due to the impact of environmental factors [ 3 ]. In cattle knowledge about the etiology of cataract development (due to genetic or environmental factors) is still relatively scarce, even though an incidence of 26% was reported in some herds [ 4 ]. Cataracts have already been observed in several cattle breeds, such as Holstein Friesian [ 5 8 ], Jersey [ 9 , 10 ], Hereford [ 11 ], Aberdeen Angus [ 11 ], Shorthorn [ 11 ] and Ayrshire [ 4 ].…”
Section: Introductionmentioning
confidence: 99%